2007
DOI: 10.1080/15563650601120792
|View full text |Cite
|
Sign up to set email alerts
|

Aminotransferase activities in healthy subjects receiving three-day dosing of 4, 6, or 8 grams per day of acetaminophen

Abstract: In a multiple-dose pharmacokinetics study of 4, 6, and 8 g/d of acetaminophen for 3 days, multiple aminotransferase determinations demonstrated no clinically important elevations at 1, 1.5, or 2 times the maximum recommended acetaminophen dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…However, another more recent study in which subjects included consumed one or two alcoholic beverages per day detected only mild elevations of liver enzymes within the normal range following the intake of up to 4 g/day paracetamol [10]. In line with the latter study, Temple et al [11] demonstrated that patients with impaired liver function neither had higher NAPQI levels nor liver enzyme elevations following repeated doses of 4 g/day paracetamol. Other studies support the view that short-term use of paracetamol at 4 g/day in alcoholics, particularly when abstinent, and subjects with hepatitis C virus (HCV) infection is safe [12,13].…”
Section: Acetaminophen/paracetamolsupporting
confidence: 59%
“…However, another more recent study in which subjects included consumed one or two alcoholic beverages per day detected only mild elevations of liver enzymes within the normal range following the intake of up to 4 g/day paracetamol [10]. In line with the latter study, Temple et al [11] demonstrated that patients with impaired liver function neither had higher NAPQI levels nor liver enzyme elevations following repeated doses of 4 g/day paracetamol. Other studies support the view that short-term use of paracetamol at 4 g/day in alcoholics, particularly when abstinent, and subjects with hepatitis C virus (HCV) infection is safe [12,13].…”
Section: Acetaminophen/paracetamolsupporting
confidence: 59%
“…Consistent with the safety of paracetamol, short term studies (3 days) on even supratherapeutic doses (6 and 8 g daily) administered to healthy subjects found that paracetamol showed very slight increases in aminotransferases but no significant hepatotoxicity (Temple et al 2007). More recently, nearly 700 patients were given 6 g paracetamol daily for 3 days without any significant liver impairment (den Hertog et al 2009).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, the vast majority of APAP users take the drug safely and without incident [21]. Although it has been demonstrated that doses of 4 grams daily over the course of 2 weeks given to healthy volunteers can lead to marked, but clinically silent, elevations in ALT and AST in more than 40% of subjects [22], other groups have not shown significant ALT elevations with doses up to 8 grams daily when used for shorter periods [23,24], including in patients who have recently used alcohol [25]. The issue of "therapeutic misadventure", a termed coined by Maddrey and Zimmerman in the mid-1990s [26], is still a cautionary tale, in that unsuspecting chronic alcohol users (which can include cirrhotics), may experience an inadvertent overdose from APAP (in doses far lower than the traditional 10 grams implicated in most intentional overdoses) leading to acute on chronic liver failure.…”
Section: Discussionmentioning
confidence: 96%